Health‐related impairments in young children with ADHD: a community‐based study. (12th June 2016) - Sciberras, E.; Bisset, M.; Hazell, P.; Nicholson, J. M.; Anderson, V.; Lycett, K.; Jongeling, B.; Efron, D.
Abstract: Background: We aimed to examine health‐related impairments in young children with attention‐deficit/hyperactivity disorder (ADHD) and non‐ADHD controls and explore differences in children with ADHD by gender, ADHD subtype and mental health co‐morbidity status. Methods: Children with ADHD ( n = 177) and controls ( n = 212) aged 6–8 years were recruited across 43 schools in Melbourne, Australia following a screening (Conners 3 ADHD Index) and case confirmation procedure (Diagnostic Interview Schedule for Children IV). Direct and blinded assessments of height and weight were used to calculate body mass index z ‐score and to identify overweight/obesity. Parents reported on child global health, sleep problems and physical injuries. Unadjusted and adjusted (socio‐demographic factors and co‐morbidities) logistic and linear regression were conducted to compare health‐related impairments between (1) children with and without ADHD; (2) boys and girls with ADHD; (3) children with ADHD‐inattentive and ADHD‐combined types; and (4) children with ADHD by internalizing and externalizing disorder status. Results: Children with ADHD had poorer global health than controls when adjusted for socio‐demographic characteristics (OR: 2.0; 95% CI 1.1, 3.9); however, this attenuated after adjusting for co‐morbidities. In adjusted analyses, children with ADHD had increased odds of moderate/large sleep problems (OR: 3.1; 95% CI 1.4, 6.8), compared with controls. There were no differences between children with and without ADHD in terms of physical injuries or overweight/obesity. Findings were similar when excluding children taking ADHD medication, and health‐related impairments did not differ between boys and girls with ADHD. Children with ADHD‐combined type had higher BMI z ‐scores than controls in adjusted analyses ( P = 0.04). Children with ADHD and co‐occurring internalizing and externalizing co‐morbidities were particularly vulnerable to health‐related impairments. Conclusion: Young children with ADHD experience a number of health‐related impairments, which are exacerbated by the presence of internalizing and externalizing co‐morbidities. Clinicians should consider the broader health of children with ADHD in clinical consultations.